2021
DOI: 10.1113/jp281114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron manipulation on hypoxic pulmonary vasoconstriction and pulmonary reactivity during ascent and acclimatization to 5050 m

Abstract: Key points Iron acts as a cofactor in the stabilization of the hypoxic‐inducible factor family, and plays an influential role in the modulation of hypoxic pulmonary vasoconstriction. It is uncertain whether iron regulation is altered in lowlanders during either (1) ascent to high altitude, or (2) following partial acclimatization, when compared to high‐altitude adapted Sherpa. During ascent to 5050 m, the rise in pulmonary artery systolic pressure (PASP) was blunted in Sherpa, compared to lowlanders; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 79 publications
(182 reference statements)
4
22
0
Order By: Relevance
“…In response to decreased inspiratory O 2 partial pressure at high altitudes, erythropoiesis occurs to increase O 2 availability and enhance iron consumption, which can lead to iron deficiency. [6][7][8][9][10] In this study, the physiological mechanisms underlying the replenishment of iron and O 2 and the association with high altitudeinduced thromboembolic disorders were investigated. We report that the plasma concentration of transferrin, a known iron transporter, was significantly elevated in human plasma at high altitude (Figure 1H).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to decreased inspiratory O 2 partial pressure at high altitudes, erythropoiesis occurs to increase O 2 availability and enhance iron consumption, which can lead to iron deficiency. [6][7][8][9][10] In this study, the physiological mechanisms underlying the replenishment of iron and O 2 and the association with high altitudeinduced thromboembolic disorders were investigated. We report that the plasma concentration of transferrin, a known iron transporter, was significantly elevated in human plasma at high altitude (Figure 1H).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Indeed, previous studies have reported low serum iron levels and bioavailability at high altitudes. [6][7][8][9][10] Therefore, iron deficiency may increase health risks for residents at high altitude and can lead to the upregulation of transferrin, an endogenous plasma protein that binds to and transports iron. 11…”
Section: Introductionmentioning
confidence: 99%
“…The PASP and Q T measurements were measured using ultrasound, an indirect method of assessing pulmonary pressure and pulmonary blood flow. However, these methods have been recommended by the American Society of Echocardiography (Quiñones et al., 2002) and shown to be adequate for these measures for the changes expected (Duke et al., 2016; Patrician, Spajić et al., 2021; Willie et al., 2021). Furthermore, any error in measurement using these methods would be similar across both Divers and Controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, alveolar hypoxia increases pulmonary artery systolic pressure (PASP) in both men and women but the magnitude has been reported to be greater on average in women as compared to men (15). Notably, alveolar hypoxia-induced increases in PASP have been reported to be 50% higher in individuals with ID or IDA compared to sexmatched, iron-replete individuals (16) and intravenous iron supplementation has been shown to attenuate hypoxia-induced increases in PASP in both iron-replete and iron-deficient humans (17)(18)(19)(20). Thus, it is possible that iron status may drive previously reported sex differences in PASP in hypoxia.…”
Section: Physiological Outcomes Where Iron Status May Impact Sex Comparisonsmentioning
confidence: 99%